Identification of introgressed rice lines of Binadhan-7×FL-378 under salt stress through SSR markers (Journal of the Bangladesh Agricultural University, 2013)
Thirty two rice lines of BC1F1 population (Binadhan-7/FL 378) were used to identify introgressed rice lines for salt tolerance using SSR markers at the Plant Breeding and Biotechnology Divisions of Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh. Seeds of BC1F1 population of Binadhan-7/FL-378 were collected from backcross population of F1 (Binadhan-7/FL 378). Salt tolerant genotype, FL-378 was crossed with high yielding variety, Binadhan-7. Randomly selected 32 BC1F1 progenies along with their two parents (Binadhan-7, FL-378) were genotyped with microsatellite or SSR markers for identification of introgressed rice lines. Parental polymorphism survey was assayed by 8 SSR markers and three polymorphic SSR markers viz., RM296, RM585 and OSR30 were selected to evaluate BC1F1 rice lines for salt tolerance. Primer RM585 indicated 16 lines as introgressed and 16 lines as susceptible in comparison with salt tolerant parent FL-378 and salt susceptible parent Binadhan-7. Primer RM296 identified 13 introgressed, and 19 susceptible lines. Nine introgressed and 23 susceptible lines were identified when BC1F1 lines were evaluated with marker OSR30. Line BC1F1-30, BC1F1-40, BC1F1-2, BC1F1-16 and BC1F1-34 were identified as introgressed in comparison with parent FL-378 (salt tolerant) when RM585 and RM296 markers were used but line BC1F1-1 and BC1F1-3 were identified as introgressed incase of 3 primers (RM585, RM296 and OSR30). Again the lines BC1F1-5, BC1F1-24, BC1F1-26, BC1F1-27, BC1F1-29, BC1F1-31, BC1F1-37 and BC1F1-38 were found susceptible as compared with parent Binadhan-7 when marker RM585, RM296 and OSR30 were used. The polymorphism information content (PIC) values ranged from 0.3290 to 0.3671 with an average of 0.3544. The overall gene diversity of SSR loci for the 32 BC1F1 rice lines along with two parents was 0.4614, ranging from 0.4152 to 0.4844. Positive correlations were found between the genetic diversity and the maximum number of repeats. Among the lines, all the loci were polymorphic and clearly distinct and the cluster analysis (NJ tree and UPGMA) showed nearly similar pattern of variation which could be used for improvement of salt tolerant rice lines of rice through SSR markers. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14680 J. Bangladesh Agril. Univ. 10(2): 185190, 2012